Evaluation of information literacy programs in selected school libraries in Metro Manila - Natino, Venica Nadine D.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Despite school libraries' efforts to impart information literacy, the increasing amount of resources and platforms for information mixed with the proliferation of fake news in the Philippines continue to infect the minds of many Filipinos. To understand the disjuncture between the efforts of increasing information literacy and continuous sharing and liking of fake news, the study focused on the practices of school librarians, teachers, staff, and school administrators in implementing information literacy programs. With data gathered through interviews with school librarians, distribution of survey to teachers, staff, and school administrators, and observation of selected school libraries, the study's findings show that the selected school libraries: 1) follow a general vision- mission statement; 2) They conduct library orientations but only Ateneo Junior High School performs a distinct program for the students and; 3) Stakeholders' collaborations are limited to scheduling and consultations.
In lieu of these results, it is suggested that the selected school libraries create a vision-mission statement and that they become proactive partners and collaborators so that, students receive quality programs and become better equipped to ward off misinformation and misleading claims.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information literacy -- Philippines; School libraries -- Reference services